Optimalisasi Potensi dan Pemanfaatan Artificial Intelligence (AI) dalam Mendukung Pembelajaran di Era Society 5.0 - Zebua, Nofamataro (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This article aims to explore the opportunities of optimizing Artificial Intelligence (AI) in supporting adaptive, inclusive, and innovative learning in the Society 5.0 era. With its potential to revolutionize education through content personalization, responsive learning, and administrative efficiency, AI is the key to future education transformation. The research approach is qualitative through literature analysis and case studies, covering the implementation of AI in adaptive learning, educational chatbots, and virtual reality technology. The researcher's review of several studies revealed that AI not only eases the administrative burden on teachers, but also provides individually tailored learning plans and improves students' digital literacy. However, the integration of AI in education faces challenges such as resistance to change and disparities in access to technology. To overcome these challenges, the development of inclusive policies as well as AI-based training for educators is recommended, thus ensuring the ethical and effective application of technology, in line with the humanistic and future-oriented vision of Society 5.0.